2014
DOI: 10.1186/1744-8603-10-29
|View full text |Cite
|
Sign up to set email alerts
|

UK medical tourists in Thailand: they are not who you think they are

Abstract: BackgroundTravel for medical treatment is an aspect of globalization and health that is comparatively less understood. Little is known about volume, characteristic and motivation of medical tourists, limiting understanding of effects on health systems and patients. Thailand is amongst a handful of countries that have positioned themselves as medical tourism destination. This paper examines in unprecedented detail volume and characteristics of medical tourists who travel from the UK to Thailand for treatment.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 22 publications
2
26
1
Order By: Relevance
“…However, this study and others have found that most such tourists travel to Thailand for minor elective procedures, such as cosmetic surgery 31 . In contrast, we found that medical tourists visiting Thailand from the United Arab Emirates were generally purchasing services such as cardiac catheterization, angiocardiograms, other cardiovascular procedures and gastric bypasses.…”
Section: Discussioncontrasting
confidence: 73%
“…However, this study and others have found that most such tourists travel to Thailand for minor elective procedures, such as cosmetic surgery 31 . In contrast, we found that medical tourists visiting Thailand from the United Arab Emirates were generally purchasing services such as cardiac catheterization, angiocardiograms, other cardiovascular procedures and gastric bypasses.…”
Section: Discussioncontrasting
confidence: 73%
“…Data on the total numbers of people travelling to seek health services in Thailand is uncertain given different classification systems and definitions and a lack of systematic research. A recent study of patient records from five largest private hospitals in Thailand found that a total of 104, 830 'medical tourists' visited in 2010, accounting for 324, 926 separate visits and generating 180 million USD (Noree et al, 2014). The top three countries of origin of patients to Thailand in 2010 were UAE (accounting for twenty percent of total foreign patients), Bangladesh and USA, followed by Myanmar, Oman and Qatar, then the United Kingdom (Noree et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…A recent study of patient records from five largest private hospitals in Thailand found that a total of 104, 830 'medical tourists' visited in 2010, accounting for 324, 926 separate visits and generating 180 million USD (Noree et al, 2014). The top three countries of origin of patients to Thailand in 2010 were UAE (accounting for twenty percent of total foreign patients), Bangladesh and USA, followed by Myanmar, Oman and Qatar, then the United Kingdom (Noree et al, 2014). There has been a major increase in patients particularly from the Gulf Cooperation Council Countries many through tie-in contracts to supply care.…”
Section: Introductionmentioning
confidence: 99%
“…Government efforts to provide better healthcare services are yet to be realised [5]. With the globalisation of healthcare, many patients from developed countries in Asia are travelling to Thailand, India and Malaysia for obtaining 'first world treatment at third world prices' [1,6,7,8,9,10,11,12]. Patients from developed and developing countries compare worldwide healthcare service quality, waiting times, cost, post-surgery care, and search for value in healthcare, relative to their own countries.…”
Section: Introductionmentioning
confidence: 99%